Drowned night : a novel of the Abbadon Inn - Blaine, Chris (Berkley horror, 2005)
In this third novel set at the Abbadon Inn, burned-out New York City cop Ted McShane and his wife Liz arrive in Cape May, New Jersey, as the inn's new proprietors. A series of disturbing occurrences strike locals with the fear that a legendary, bloodthirsty creature has been roused.